2023
DOI: 10.1161/strokeaha.122.038466
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Ineffective Reperfusion After Endovascular Therapy in Acute Ischemic Stroke

Abstract: Endovascular treatment is a highly effective therapy for acute ischemic stroke due to large vessel occlusion. However, in clinical practice, nearly half of the patients do not have favorable outcomes despite successful recanalization of the occluded artery. This unfavorable outcome can be defined as having clinically ineffective reperfusion. The objective of the review is to describe clinically ineffective reperfusion after endovascular therapy and its underlying risk factors and mechanisms, including initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 89 publications
0
27
0
1
Order By: Relevance
“…Unfortunately, since TR was not available in our study, we could not further examine this correlation. The independent association of BPV with clinical outcomes, but not with sICH, could be partly explained by the possibility of sustained hypoperfusion despite EVT (leading in turn to reactive BP elevation and variability), 49,50 rather than the reperfusion injury and sICH per se. This hypothesis argues against the intensive BP lowering to avoid the latter and to improve clinical outcomes among EVT-treated patients.…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately, since TR was not available in our study, we could not further examine this correlation. The independent association of BPV with clinical outcomes, but not with sICH, could be partly explained by the possibility of sustained hypoperfusion despite EVT (leading in turn to reactive BP elevation and variability), 49,50 rather than the reperfusion injury and sICH per se. This hypothesis argues against the intensive BP lowering to avoid the latter and to improve clinical outcomes among EVT-treated patients.…”
Section: Discussionmentioning
confidence: 95%
“…This paper studied the prediction of futile recanalization from two aspects: collateral circulation status evaluation and In ammatory response level. Previously reported that the mechanism of futile recanalization may be related to reperfusion injury and the "No-re ow" phenomenon [9]. In addition, the patency of collateral circulation can effectively identify reperfusion and determine the infarct size and even the clinical outcome of AIS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, nearly half of the successful recanalization patients tend to have a poor prognosis and futile recanalization [4][5][6]. Since the mechanism of futile recanalization is not clear, many conclusions are inseparable from reperfusion injury [7][8][9]. Rapid blood ow to ischemic brain tissue provokes a cascade of in ammatory reactions and oxidative stress, leading to cellular and blood-brain barrier damage, which ultimately manifests as neurological deterioration [10].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is defined as severe tissue hypoperfusion despite timely recanalization of an occluded artery, which may be due to abnormalities at the level of the microvasculature. Microvascular obstruction from endothelial cell swelling, pericyte contraction, luminal clogging with leukocytes and microthrombi can impede the reperfusion after EVT because EVT only clears blockages in large arteries ( Nie et al, 2023 ). In clinical studies, the incidence of the no-reflow phenomenon after EVT has ranged from 25 to 38% ( Ng et al, 2018 ; Rubiera et al, 2020 ; Ter Schiphorst et al, 2021 ).…”
Section: Anesthetics May Affect the Outcomes Of Evtmentioning
confidence: 99%